2021
DOI: 10.1172/jci137845
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced triacylglycerol catabolism by carboxylesterase 1 promotes aggressive colorectal carcinoma

Abstract: The ability to adapt to low-nutrient microenvironments is essential for tumor-cell survival and progression in solid cancers, such as colorectal carcinoma (CRC). Signaling by the NF-κB transcription-factor pathway associates with advanced disease stages and shorter survival in CRC patients. NF-κB has been shown to drive tumor-promoting inflammation, cancer-cell survival and intestinal epithelial cell (IEC) dedifferentiation in mouse models of CRC.However, whether NF-κB affects the metabolic adaptations that fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Mechanistically, we found that Ces1d/CES1 promotes CRC cell survival via at least two cell-autonomous mechanisms: 1) It increases TAG and CE breakdown to mobilize endogenous FFAs and produce ATP by FAO during starvation, thus enabling CRC cells to meet their energy demand; 2) it prevents the toxic buildup of neutral lipids that results in ROS production and phospholipid peroxidation, triggering apoptosis and ferroptosis 16 ( Figure 1 ). Accordingly, CES1 inhibition by knockdown or small molecules resulted in CRC cell death upon starvation in vitro and suppression of CRC growth in mouse xenograft models in vivo .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanistically, we found that Ces1d/CES1 promotes CRC cell survival via at least two cell-autonomous mechanisms: 1) It increases TAG and CE breakdown to mobilize endogenous FFAs and produce ATP by FAO during starvation, thus enabling CRC cells to meet their energy demand; 2) it prevents the toxic buildup of neutral lipids that results in ROS production and phospholipid peroxidation, triggering apoptosis and ferroptosis 16 ( Figure 1 ). Accordingly, CES1 inhibition by knockdown or small molecules resulted in CRC cell death upon starvation in vitro and suppression of CRC growth in mouse xenograft models in vivo .…”
mentioning
confidence: 99%
“…Using the Consensus Molecular Subtype (CMS) CRC classification, 15 we discovered an intrinsic linkage of obesity with constitutive activation of NF-κB transcription factors, tumor-based inflammation, and fat catabolism in the mesenchymal CMS4 subtype, associated with stemness, stromal infiltration, EMT, and shorter overall survival (OS) and relapse-free survival (RFS) in CRC patients. 16 By conducting a combined metabonomic and gene expression profiling, we identified carboxylesterase 1 (CES1) as an essential NF-κB-regulated TAG and CE lipase promoting tumor cell survival and metabolic adaptation in aggressive CRC. 16 Increased CES1 expression correlated with worse clinical outcomes in overweight, but not non-overweight CRC patients and was enriched downstream of NF-κB in CMS4 tumors, thus providing a mechanism for the aggressive clinical behavior of obesity-associated CRC and a potential therapeutic route that relates to the core biological underpinnings of tumor subtypes ( Figure 1 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations